972 views
4 votes
Help me on this question in the photo asap

Help me on this question in the photo asap-example-1
User RobinXSI
by
4.3k points

1 Answer

3 votes

Answer:

a. -5 b. 23 c. 871 d. -5

Explanation:

f(x) = x^2 + 6x and g(x) = x - 4

a). (fog)(3) = (x - 4)^2 + 6(x - 4)

= (3 - 4)^2 + 6(-1)

= 1 -6

= -5

b). (gof)(3) = ( x^2 + 6x) - 4

= (9 + 18) - 4

= 23

c). (fof)(3) = (x^2 + 6x)^2 + 6(x^2 + 6x)

= 27^2 + 27(6)

= 871

d). (gog)(3) = (x - 4) -4

= (3 - 4) - 4

= -5

User Mike Wise
by
4.8k points